Nurse-patient communication experiences from the perspective of Iranian cancer patients in an outpatient oncology clinic: a qualitative study - Afsaneh Azarabadi; Farzaneh Bagheriyeh; Yaser Moradi; Samira Orujlu (BMC, 2024)
Abstract Background Effective communication between nurses and cancer patients is essential for patient satisfaction and optimal health outcomes in outpatient oncology settings. This study explored the communication experiences of Iranian cancer patients receiving outpatient treatment. Methods Semi-structured interviews were conducted with 14 adult cancer patients undergoing chemotherapy, radiotherapy, or follow-up treatment at an outpatient clinic in Urmia, Iran. Qualitative content analysis was used to analyze the data. This study adhered to the standards set forth in the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Results Three main categories emerged from the interviews with Iranian cancer patients: communication dynamics, barriers to communication, and effective communication outcomes. Patients expressed a desire for nurses who actively listen, provide emotional support, and offer thorough education about their disease and treatment options. However, they also identified barriers to effective communication, including negative nurse behaviors (such as lack of empathy), heavy workloads, gender and language discordance, and logistical challenges within the clinic setting. When communication was positive, patients reported increased commitment to their treatment plans, improved coping mechanisms, reduced stress levels, and greater satisfaction with their overall care. Conclusions This study revealed the multifaceted nature of communication in outpatient oncology settings from the patient's perspective. Findings underscore the need for interventions that enhance nurse communication skills, address workload issues, promote cultural sensitivity, and optimize clinic logistics. These efforts can significantly improve patient experiences and treatment outcomes during cancer treatment.